2000
DOI: 10.1111/j.1365-2133.2000.03718.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of squamous cell carcinoma by two high-risk human papillomaviruses (HPVs), a novel HPV-67 and HPV-31 from bowenoid papulosis

Abstract: We report a patient with bowenoid papulosis (BP) involving two high-risk human papillomaviruses (HPVs) and the development of invasive squamous cell carcinoma (SCC). Our patient showed verrucous lesions on the penis, perianal area and groin that had been noted over the previous 8 years and had recurred after all therapeutic approaches. The perianal and left inguinal lesions revealed invasive SCC on histology. HPV-31 and HPV-67 sequences were detected by polymerase chain reaction from BP lesions of the perianal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…However this does not exclude malignant changes at a later time point, since the development, maintenance and progression of precursor lesions evolve slowly into invasive cancer, typically over a period of more than 10 years [27]. Yoneta and co-workers reported that a patient with Bowenoid papulosis involving HPV31, 67 infection developed invasive squamous cell carcinoma (SCC) 8 years following the Bowenoid papulosis' diagnosis [28]. Therefore a longer follow up time may be valuable for those Condyloma acuminatum patients who experienced HPV16/18 and/or HPV31/33 infection.…”
Section: Discussionmentioning
confidence: 99%
“…However this does not exclude malignant changes at a later time point, since the development, maintenance and progression of precursor lesions evolve slowly into invasive cancer, typically over a period of more than 10 years [27]. Yoneta and co-workers reported that a patient with Bowenoid papulosis involving HPV31, 67 infection developed invasive squamous cell carcinoma (SCC) 8 years following the Bowenoid papulosis' diagnosis [28]. Therefore a longer follow up time may be valuable for those Condyloma acuminatum patients who experienced HPV16/18 and/or HPV31/33 infection.…”
Section: Discussionmentioning
confidence: 99%
“…No malignant changes were found in 54 BP patients after 5 years of follow-up [3]. Recently, however, 10 cases of SCC developed from BP, including the present case, have been reported [5, 6, 7, 8, 9, 10, 11, 12]. Associations have been reported in 5 cases (thyroid and colon cancer [6], uterine cervical cancer [8], HIV infection [9], leukemia [10], pancytopenia in the present case).…”
Section: Discussionmentioning
confidence: 95%
“…The cervical cancer with HPV infection is categorized in a mucosal high-risk group. Five cases of BP including the present one showed the presence of HPV-31 DNA [12, 14, 15, 16]. Three cases showed depressed immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Das Tumorwachstum beginnt in der Regel nicht de novo; es entsteht meist auf vorgeschädigter Haut, wie beispielsweise bei Kondylombefall [1,4,11,13,14,20], bei Lichen ruber planus [5], Acne inversa [7,12,15,19], Morbus Crohn [10,16] und Lichen sclerosus et atrophicans [3,17,18]. Eine Immunsuppression begünstigt die Tumorentstehung [6,9].…”
Section: äTiopathogeneseunclassified